2012
DOI: 10.1016/j.funeco.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Fungal grass endophytes and arthropod communities: lessons from plant defence theory and multitrophic interactions

Abstract: Abstract:Alkaloids produced by systemic fungal endophytes of grasses are thought to act as defensive agents against herbivores. Endophytic alkaloids may reduce arthropod herbivore abundances and diversity in agronomic grasses. Yet, accumulating evidence, particularly from native grasses, shows that herbivore preference, abundances and species richness are sometimes greater on endophyte-infected plants, even those with high alkaloids, contrary to the notion of defensive mutualism. We argue that these conflictin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 83 publications
(111 reference statements)
0
28
1
Order By: Relevance
“…The mechanism of interaction between the endophytic fungi and their host plants has still not been completely understood, mainly from the stand point of chemistry, since it has been known that they live in a neutral or even mutualistic interaction with host plants. Fungi are good producers of secondary metabolites, many with the same biological activity (Rosa et al 2010;Chandra 2012;Pinheiro et al 2013), where some compounds may help the host plant with combating infestation by other fungi, viruses and bacteria (Faeth and Saari 2012;Kusari et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of interaction between the endophytic fungi and their host plants has still not been completely understood, mainly from the stand point of chemistry, since it has been known that they live in a neutral or even mutualistic interaction with host plants. Fungi are good producers of secondary metabolites, many with the same biological activity (Rosa et al 2010;Chandra 2012;Pinheiro et al 2013), where some compounds may help the host plant with combating infestation by other fungi, viruses and bacteria (Faeth and Saari 2012;Kusari et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In North American grasslands, Clay et al (2005) manipulated both insect herbivores and vertebrate grazers, and only found significant increases in endophyte frequencies when both were present. Invertebrate herbivores may generally be more important than vertebrates in driving infection frequencies due their chronic and persistent herbivory, transmission of plant diseases and pathogens, and consumption of both below-and above-ground tissues (Faeth and Saari 2012). Studies quantifying invertebrate herbivory within rabbit exclosures of different ages are needed to better understand the combined effects of rabbits and invertebrates in affecting endophyte frequencies in our system.…”
Section: Alternate Hypotheses Explaining Endophyte Dynamics In the Fieldmentioning
confidence: 99%
“…Such variation in native grass performance in response to endophytes may explain the highly variable infection frequencies found in natural populations, which range from 0% to over 50% (Wäli et al 2007;Iannone et al 2011). Thus, while endophytes do not appear ubiquitously mutualistic in wild grasses, there have been far fewer studies examining the effects of endophytes in natural systems, and long-term studies testing the defensive mutualism hypothesis are rare (Faeth and Saari 2012; but see Rudgers and Clay 2008;Jani et al 2010;Faeth and Shochat 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These symbionts grow asymptomatically within the aerial parts of the host tissue, including the seeds through which they are vertically transmitted to the next generation. This relationship, which is obligate for the endophytic fungus and facultative for the plant, is considered a true mutualism because of many reciprocal benefits such as stress tolerance, increased competitive abilities and, most well known, resistance against herbivores (Clay and Schardl 2002;Faeth and Saari 2012;Popay and Hume 2011;but see Faeth 2002). The latter is attributed primarily to the range of alkaloids (peramine, ergot alkaloids, lolitrems, lolines) that the various endophyte species produce in the aerial parts of the plant and which in some associations are translocated to the roots, albeit in lower concentrations (Omacini et al 2012;Patchett et al 2008;Saikkonen et al 2013).…”
mentioning
confidence: 99%
“…The latter is attributed primarily to the range of alkaloids (peramine, ergot alkaloids, lolitrems, lolines) that the various endophyte species produce in the aerial parts of the plant and which in some associations are translocated to the roots, albeit in lower concentrations (Omacini et al 2012;Patchett et al 2008;Saikkonen et al 2013). Enhanced resistance against insects seems to be more prevalent in agronomic grasses due to artificial selection for endophytes with desired traits than in natural grassland communities where greater variation exists as a result of evolutionary adaptations by specialist herbivores (Faeth and Saari 2012). However, evidence for the protective effects of endophytes in wild grasses is increasing (Raman et al 2012).…”
mentioning
confidence: 99%